Levantamento etnoveterinárioaplicado à caprinocultura em assentamentos rurais de Mossoró - Rio Grande do Norte - Souza, Thulianne Lopes de (2015)
Ethnoveterinary research is defined as the science that involves the opinion and knowledge of popular practices, used for the treatment and prevention of diseases that affect animals. Among the branches of this science is herbal medicine consisting in the treatment of diseases using medicinal plants, this practice is becoming more widespread, and it is evident in fact, because of the valuable lessons of past generations and the future treatment of humans and animals may replace or reduce the use of synthetic drugs, allowing the existence of a means balancing at room. With this research attempts to revive the popular knowledge about the use of medicinal plants in goats in rural settlements, located in the municipality of Mossoró/RN, Northeastern Brazil, and to achieve this goal have been made visits to settlements, applying questionnaires to producers of goats that live in these places on therapeutic indications and ways of using plants to treat diseases that these animals.Simultaneously were collected copies of the said plants, whichthey were identified and deposited in the herbarium MOSS, Federal Rural University of the Semiarid.The medicinal uses have been described 38 species belonging to 23 botanical families, reported by 106 respondents aged over 18 years. The families of plants with the largest representation in the consultation were Fabaceae (7 spp.), Euphorbiaceae (4 spp.), Lamiaceae (3 spp.). The most frequent species were Heliotropium indicum L. (Fedegoso), Ximenia americana L. (Ameixa- brava) e Aloe vera(babosa). The bark and the leaves were predominantly the parties mentioned. The data collected by this research showed that farmers goats, have access and knowledge to a wide variety of medicinal plants responsible for supplying different diseases that affect goats. And it can be seen that even with today's technological advances the groupin this study has interest in the use of plants for medicinal purposes